Complete mitochodrial genome of Spinibarbus caldwelli (Cypriniformes, Cyprinidae). (31st July 2013) - Ai, Weiming; Peng, Xin; Huang, Xiaolin; Xiang, Dan; Chen, Xiao
Abstract: The complete mitochondrial genome of S. caldwelli was determined in this study. The gene composition, arrangement and transcriptional orientation in S. caldwelli mitogenome were identical to most vertebrates. Two start codon patterns (ATG and GTG) and three stop codon patterns (TAG, TAA and T) were found in protein-coding genes. Only the tRNA- Ser2 could not fold into a typical clover-leaf secondary structure for lacking the dihydrouridine arm. Sequences alignment results suggest that the complete mitogenome of S. caldwelli is an efficient tool to check species identification by comparing different gene sequences.